Nutritional Status of Women Living at South-west Coastal Belt of Satkhira Bangladesh (Journal of Environmental Science and Natural Resources, 2016)
Malnutrition has long been regarded as a widespread public health problem especially in the poorest part of Bangladesh. For determining nutritional status of women living in South-West coastal belt of Bangladesh, in this regard, Shyamnagar Upazilla of Satkhira district was selected. A random questionnaire survey was conducted by pre scheduled structured questionnaire among the 6 villages from Gabura and Munshiganj union of the Shyamnagar UpaziIla during November, 2012 to January, 2013. A total of 120 households (preferably women) were randomly selected from the six study villages based on mainly livelihood pattern of the households such as crop production, shrimp culture and Sunderbans depended activities. In the study area, about 54.17% women had BMI of 18.5-24.9 and mean body weight of 49.75 ± 8.36 kg. About 79.16% families had vegetable gardens around their houses and they were gardening mainly for consumption and additional income of the family. Most of the families could not afford to enough eat more egg, fish or meat after Aila occurred because of low availability due to soil salinity. Salinity caused many diseases; skin disease was one of them. About 28% families bought food in credit and 20.14% respondents in Gabura and 31.59% in Munshiganj paid their loan at Pohela Boishakh. They received treatment facilities for their health hazards from village doctors and public health centre during the period of disease occurred. This study concluded that salinity affect the livelihood and nutrition on the community of the coastal belt.J. Environ. Sci. & Natural Resources, 8(2): 41-46 2015